Improving English Vocabulary through the Use of Flashcards in Learning English as a Foreign Language In Seventh Grade at Junior High School - Febryanti, Feby; Patmasari, Andi; Kamaruddin, Abdul; Thamrin, Nur Sehang (EDUMALSYS Journal of Research in Education Management, 2025)
The objective of this research is to find out if using flashcards can improve the student’s vocabulary mastery in junior high school. This research used a quasi-experimental research design. The population of this research was the seventh grade students of SMPN 1 Lore Timur. The sample was selected using the purposive sampling technique. The sample of this research were 53 students, which were divided into 27 the students of class D as an experimental group and 26 students of class A as a control group. The data were collected through the test that consisted of pre-test and post-test. By applying the independent t-test, the researcher found there is no significant difference between the experimental and control groups (p = 0.147, p > 0.05). Thus, the hypothesis was rejected, using flashcards can't improve the student vocabulary mastery in seventh grade at junior high school.